2021
DOI: 10.1038/s41467-021-22234-9
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide binding potential and regulatory activity of the glucocorticoid receptor’s monomeric and dimeric forms

Abstract: A widely regarded model for glucocorticoid receptor (GR) action postulates that dimeric binding to DNA regulates unfavorable metabolic pathways while monomeric receptor binding promotes repressive gene responses related to its anti-inflammatory effects. This model has been built upon the characterization of the GRdim mutant, reported to be incapable of DNA binding and dimerization. Although quantitative live-cell imaging data shows GRdim as mostly dimeric, genomic studies based on recovery of enriched half-sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
48
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(56 citation statements)
references
References 65 publications
(112 reference statements)
7
48
0
1
Order By: Relevance
“…Although a further reduction in dimerization in the double mutant cells compared to GR D/D could not be demonstrated, the double mutation led to another 50% (from 20% gene expression increase J o u r n a l P r e -p r o o f compared to controls to 10% gene expression increase) reduction the of gene induction capacity of GRE genes compared to GR D/D cells, which already showed only fraction of activity compared to GR wt/wt cells. These results are in agreement with the recently published study by Johnson et al (46), where an in-depth in vitro comparison of the GR wt/wt , GR D/D and GR D+L /D+L genotypes was performed. However, we found that GR L/L cells displayed a significant residual dimerization as well as only a 50% reduction on dimer mediated transcriptional activation as compared to GR wt/wt .…”
Section: J O U R N a L P R E -P R O O Fsupporting
confidence: 93%
See 1 more Smart Citation
“…Although a further reduction in dimerization in the double mutant cells compared to GR D/D could not be demonstrated, the double mutation led to another 50% (from 20% gene expression increase J o u r n a l P r e -p r o o f compared to controls to 10% gene expression increase) reduction the of gene induction capacity of GRE genes compared to GR D/D cells, which already showed only fraction of activity compared to GR wt/wt cells. These results are in agreement with the recently published study by Johnson et al (46), where an in-depth in vitro comparison of the GR wt/wt , GR D/D and GR D+L /D+L genotypes was performed. However, we found that GR L/L cells displayed a significant residual dimerization as well as only a 50% reduction on dimer mediated transcriptional activation as compared to GR wt/wt .…”
Section: J O U R N a L P R E -P R O O Fsupporting
confidence: 93%
“…In GR D+L/D+L mutants, a Kd 2.5x lower compared to GR wt/wt was detected. These differences in ligand affinity remain unexplained, but they might suggest that the DBD dimerization provides a ligand-affinity lowering signal, while the LBD dimerization causes an opposite signal (Figure (46). Indeed, as the GR wt/wt and GR D/D behave normally in ligand binding and translocate to the nucleus, the differences in expression can only be explained by differences in DNA binding between both receptors.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…Our live-cell imaging studies have revealed that dimeric GR might be an intermediate state towards transcriptionally active tetramers bound to target DNA sequences (Presman et al, 2016;Paakinaho et al, 2019;Johnson et al, 2021), also in line with the current SPR results. Although more speculative, it is possible to generate tentative models of DNA-bound GR tetramers that satisfy the constraints derived from current structure-function information.…”
Section: Gr Does Not Dimerize In An Ar-like Conformationsupporting
confidence: 90%
“…6B, arrowheads). Severely reduced genome-wide chromatin binding for GR mon has recently been shown (Johnson et al, 2021), and only a very small percentage of GR mon cells form visible arrays (Presman et al, 2016(Presman et al, , 2014. Interestingly, we did not detect any arrays in experiments with GR mon/Y545A (Fig.…”
Section: Residues Tyr545 and Asp641 Modulate Multimerization Of Full-length Grsupporting
confidence: 53%
“…These findings indicate that neither the beneficial nor the deleterious GC activities can be unequivocally assigned to one or the other molecular mechanism of the GR. A possible explanation for the ambiguous situation in GR dim mice is provided by the recent observation that the A458T mutation disrupts only one of the GR dimerization interfaces thus allowing some residual binding as dimers [ 195 ]. Otherwise, GR dim mice undoubtedly show a reduced transcriptional response [ 192 ], suggesting that a partial impairment of GR activity is sufficient to blunt anti-inflammatory GC effects [ 196 ].…”
Section: Novel Therapeutic Approachesmentioning
confidence: 99%